Neurobiology of Navigation and Learning: Fourth Dimension Cartography - Sepúlveda-Sariego, Agustín; Meza-Fernández, Sandra (International Journal of Engineering and Technology, 2018)
The present article sheds light on new representations of learning. The proposition deals with a representation of learning in four dimensions, in which the highlight is on the navigation across space as a new perspective on the phenomenon of learning. This perspective allows for some aspects of the phenomenon and attempts to show experimental proposals on the matter. Three of the dimensions are based on learning theories: Vigotsky’s Meaningful learning; Piaget’s self-directed learning through discovery; and Vigotsky’s Social Learning. A fourth dimension would be the physical space itself. Animals navigate in different ways through the world. Navigation: the process of being in this world is the basis of learning.